Neighboring alkenyl group participated ether-based electrolyte for wide-temperature lithium metal batteries - Tang, Jimin; Wei, Zhixuan; Wu, Junxiu; Cui, Zhuangzhuang; Tian, Ruiyuan; Jiang, Heng; Du, Fei; Lu, Jun (Nature communications, 2025)
The extensive dendrite formation and unstable interfacial chemical environment pose significant obstacles to operating lithium metal batteries under extreme conditions. Here, we develop an allyl ether electrolyte operated across a wide-temperature range. Leveraging the neighboring group participation effect of alkenyl groups, the designed electrolyte possesses a quasi-weak solvation structure with low desolvation energy. Moreover, this effect facilitates the anion decomposition to form a dual-layer solid electrolyte interface, suppressing dendrite formation and surface parasitic reactions. Therefore, the single-salt, single-solvent electrolyte enables reversible lithium plating/stripping with high Coulombic efficiencies from −40 °C to 60 °C. The assembled 50 μm lithium | |3.5 mAh cm −2 sulfurized polyacrylonitrile full cells achieve capacity retention of 93.1% after 150 stable cycles (0.2 C) at 25 °C, where the positive electrode could retain 78% of its room temperature capacity at −40 °C. Moreover, the pouch cells demonstrate promising cycling stabilities, with a capacity retention of 94.8% (0.5 C), 92.4% (0.2 C), and 72.7% (0.1 C) after 100 cycles at 60 °C, 25 °C, and −40 °C, respectively. This terminal group modification strategy offers perspectives for wide-temperature electrolyte design, representing a crucial advancement in enhancing the performance of lithium metal batteries. Lithium metal batteries are susceptible to dendrite growth and interfacial instability, particularly at extreme temperatures. Here, authors propose an allyl ether electrolyte with a neighbouring group participation in lithium solvation regulation, inducing a dual-layer SEI and enabling stable cell operation from −40 to 60 °C.